2006
DOI: 10.1111/j.1365-2788.2006.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective investigation of the sleep–wake cycle in adults with intellectual disabilities and autistic spectrum disorders

Abstract: The mean scores of the participants as a whole indicated abnormalities in the two key circadian rhythm parameters of interdaily stability and intradaily variability. The implications of these findings for both clinical practice and theory are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 40 publications
4
20
0
Order By: Relevance
“…However, there has been little work performed on adolescents and adults, with most of the reported studies focusing on childhood. Sleep parameters measured with actigraphy in adolescents and young adults with autistic disorder, Asperger syndrome and an unspecified intellectual disorder (Oyane & Bjorvatn 2005; Hare et al. 2006) suggest individuals with Williams syndrome share similar sleep patterns with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been little work performed on adolescents and adults, with most of the reported studies focusing on childhood. Sleep parameters measured with actigraphy in adolescents and young adults with autistic disorder, Asperger syndrome and an unspecified intellectual disorder (Oyane & Bjorvatn 2005; Hare et al. 2006) suggest individuals with Williams syndrome share similar sleep patterns with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This problem persists through childhood because 50-80% of children with ASD show highly significant increased sleep latency and nocturnal awakenings (Richdale and Prior 1995;Taira et al 1998;Takase et al 1998;Hering et al 1999;Elia et al 2000;Hayashi 2000;Schreck and Mulick 2000;Gail Williams et al 2004;Wiggs and Stores 2004;Limoges et al 2005;Oyane and Bjorvatn 2005;Polimeni et al 2005;Allik et al 2006;Hare et al 2006;Liu et al 2006;Malow et al 2006). An extensive survey of the sleep problems observed in ASD was recently reported by Liu et al (2006).…”
Section: Atypical Sleep and Circadian Rhythms In Autism Spectrum Disomentioning
confidence: 99%
“…SPs can be lifelong with a prevalence in childhood ranging up to 86% [Souders et al, ], whereas 44.7% of 168 autistic adults with severe intellectual disability (ID) were reported to have SPs using the DASH II questionnaire [Matson et al, ). However, Hare, Jones, and Evershed () reported that sleep measures in a small group of adults with autism and ID did not differ from adults with ID alone. Similarly, cognitively able autistic adults are reported to have increased insomnia symptoms, including increased sleep latency, poor sleep efficiency, shorter night sleep, and advanced or delayed circadian sleep–wake rhythms [Baker & Richdale, ; Baker & Richdale, ; Goldman et al, ; Hare et al, , ; Limoges, Mottron, Bolduc, Berthiaume, & Godbout, ; Tani et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hare, Jones, and Evershed () reported that sleep measures in a small group of adults with autism and ID did not differ from adults with ID alone. Similarly, cognitively able autistic adults are reported to have increased insomnia symptoms, including increased sleep latency, poor sleep efficiency, shorter night sleep, and advanced or delayed circadian sleep–wake rhythms [Baker & Richdale, ; Baker & Richdale, ; Goldman et al, ; Hare et al, , ; Limoges, Mottron, Bolduc, Berthiaume, & Godbout, ; Tani et al, ). Causes for sleep abnormalities are likely to be multifactorial, such as neurotransmitter abnormalities (e.g., serotonin) [Anderson & Lombroso, ; Malow et al, ), medical problems (e.g., gastrointestinal disorders [Klukowski, Wasilewska, & Lebensztejn, ), epilepsy (Kaleyias et al, ]), psychopathology [Nadeau et al, ; Richdale, Baker, Short, & Gradisar, ] or behavioral etiologies (e.g., poor sleep habits [Malow et al, ; Reynolds & Malow, ]).…”
Section: Introductionmentioning
confidence: 99%